2015
DOI: 10.1590/s0036-46652015000200007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites Among Food Handlers of Sari, Northern Iran

Abstract: Parasitic infection is highly prevalent throughout the developing countries of the world. Food handlers are a potential source of infection for many intestinal parasites and other enteropathogenic infections as well. The aim of this study was to determine the prevalence of intestinal parasite carriers among food handlers attending the public health center laboratory in Sari, Northern Iran for annual check-up. The study was performed from August 2011 through February 2012. Stool samples were collected from 1041… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
58
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 23 publications
13
58
14
Order By: Relevance
“…In this study, the overall prevalence of intestinal parasites among food-handlers was 33% which is in consistence with the study conducted in Wolaita, Ethiopia (33.68%) [27] and comparable with the study done in Arba Minch, Ethiopia (36.0%) [28], Nigeria (38.1%) [29], Khartoum, Sudan (30.5%) [15]. The present prevalence is higher than 20.6%% in Hawassa University, Ethiopia [30], Western Iran (9%) [31], Sari, Northern Iran (15.5%) [32]. It was lower than the prevalence of 58.4% which was from Jimma, Ethiopia [25], 41.1% from Bahirdar Town [23] and 41.1% from Yebu Town, Ethiopia [20].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the overall prevalence of intestinal parasites among food-handlers was 33% which is in consistence with the study conducted in Wolaita, Ethiopia (33.68%) [27] and comparable with the study done in Arba Minch, Ethiopia (36.0%) [28], Nigeria (38.1%) [29], Khartoum, Sudan (30.5%) [15]. The present prevalence is higher than 20.6%% in Hawassa University, Ethiopia [30], Western Iran (9%) [31], Sari, Northern Iran (15.5%) [32]. It was lower than the prevalence of 58.4% which was from Jimma, Ethiopia [25], 41.1% from Bahirdar Town [23] and 41.1% from Yebu Town, Ethiopia [20].…”
Section: Discussionsupporting
confidence: 90%
“…The overall prevalence of parasites infection was 14.2% in the current study. In the previous studies conducted on specific community groups in Mazandaran province, the prevalence rates of IPIs were reported to be 15.5%, 26.2%, 33.3%, and 12% in the food handlers, mentally challenged children, school children, and rural inhabitants, respectively [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The recent effort targeted toward the improvement of sanitation, hygiene, and overall health of people in Mazandaran province has had a positive impact on reducing the burden of intestinal parasites [11][12][13][14]. Based on the findings, it could be concluded that helminthic infections well controlled among people; however, protozoan infections are on rise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food handlers are a potential source of infection for many intestinal parasites and other enteropathogenic infections as well [1].…”
Section: Introductionmentioning
confidence: 99%